Pengaruh akuntabilitas, tekanan anggaran waktu, dan moral reasoning terhadap kualitas audit - Rabihah, Adzrah; Zakaria, Adam; Nasution, Hafifah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to analyze the effect of accountability, time budget pressure, and moral reasoning on audit quality. This study uses a quantitative approach with primary data types. The population in this study are auditors who work at the Inspectorate General of the Ministry of Religion of the Republic of Indonesia. This study used a purposive sampling method with 57 respondents from Inspectorate Region I and Region III with more than one year of experience. This study used the Partial Least Square (PLS) analysis technique which was processed using the SmartPLS 4.0 application. The results of this study indicate that accountability and moral reasoning positively affect audit quality, while time budget pressure does not affect audit quality. This means that the higher the accountability and moral reasoning of an auditor, the higher the audit quality. However, increases and decreases in time budget pressure will not affect audit quality.